Efficacy of mangosteen (Garcinia mangostana) peel hot water extract against Aeromonas hydrophila infection of seabass fingerling (Lates calcarifer) - Thiankham, S.; Thonghuatoei, W.; Kantha, P.; Yomla, R.; Kitikiew, S. (My University, 2024)
The mangosteen (Garcinia mangostana Linn.) peel hot-water extract (MPE) is proved to be antibacterial potential of seabass fingerling (Lates calcarifer) rearing in freshwater which infected by Aeromonas hydrophila. In vitro study, Minimal Inhibitory Concentration (MIC) of MPE was 25 ppm and the Minimal Bactericidal Concentration (MBC) was 25 ppm. For In vivo, fingerlings were immersed in different concentrations of MPE by 0 ppm (Control), 20 ppm, 40 ppm, and 60 ppm respectively for 7 days with A. hydrophila concentration of 108 CFU mL-1. The results showed that the group which received MPE were higher survival rate compare with control group. Hematological parameters revealed that the group that received MPE had significantly increased levels of red blood cells (RBC), white blood cells (WBC), and hemoglobin concentration (Hb) than control group. Moreover, the water quality parameters were not significantly different except ammonia concentration, at 60 ppm MPE concentration of ammonia was the lowest. All results can imply that the MPE is able to improve the antibacterial potential and culture potential for seabass fingerlings.
Keywords: Aeromonas hydrophila; Antimicrobial; Mangosteen peel extract; Seabass